Survival of different coral species transplanted under varying environmental conditions at the Hundred Islands National Park - Palomar, Mike Joshua S. (Quezon City College of Science, University of the Philippines, 2007)
Coral reefs worldwide have been seriously degraded over the past decades due to a combination of natural and anthropogenic disturbances. At the Hundred Islands National Park in Pangasinan, the Philippines, most of the reefs have been subjected to destructive fishing practices, reducing coral cover in most reef areas. This has led the Philippine Tourism Authority together with the Marine Science Institute of the University of the Philippines to embark on a coral reef restoration project to increase biodiversity at selected degraded reef areas. The main activity of the project was the transplantation of different coral species collected from remaining donor reef areas. Among the coral species transplanted and monitored over three years were Acropora microphthalma, A. echinata, A. abrolhosensis, Montipora foliosa, Pavona cactus, and Porites cylindrica. Responses to transplantation of the different coral species were variable depending on the environmental conditions (e.g. water clarity, turbulence) of the transplantation sites, and the physiological characteristics of the coral species. At the northern sector of the Hundred Islands, Porites cylindrica survived.of the transplantation sites, and the physiological characteristics of the coral species. At the northern sector of the Hundred Islands, Porites cylindrica survived moderately well after 36 months (30±17.8 %) as compared to Montipora foliosa (17±14.9 %) and Acropora microphthalma (14±6.1 %). At the central sector, P. cylindrica (57±9.6 %) and Pavona cactus (41±11.6 %) survived better than A. echinata (31±8.8 %) after 36 months. At the southern sector, all of the transplants fared relatively poorly after 36 moths (P.cylindrica -14±11.3 %; A.abrolhosensis -23±26.2 %; and P. cactus -5±11.5 %) Dominance of certain coral species at the donor reef sites appeared to relate to which coral species survived better at adjacent transplant sites.Donor reef sites where selecte coral colonies were fragmented for transplantation were monitored and assessed using different image analysis techniques. The traditional point count method (5-point system) was compared with the image analysis software Cellenger. Significant differences between methods in the estimates of percent coral and algal cover were detected. Changes in coral cover over time were only detected with the 5-point system at Cuenco Island. Significant changes in algal cover over time on the other hand were detected at Milagrosa and Cuenco islands using the 5-point system and Cellenger, respectively. Differences in the reported percent cover of coral and algae by both methods may be attributed to the accuracy of each method.
Thesis (M.S. Marine Science)--University of the Philippines Diliman
Keywords: Corals -- Alaminos -- Pangasinan -- Hundred Islands